Correlative vs. Causative Relationship between Neonatal Cranial Head Shape Anomalies and Early Developmental Delays - Andrews, Brian T.; Fontana, Stefani C. (Frontiers in Neuroscience, 2017)
Deformational plagiocephaly and craniosynostosis are two of the most common cranial head shape anomalies. Traditionally, both entities were thought to cause aesthetic concerns solely. Recent research has demonstrated that both conditions are associated with developmental delays. The relationship between the abnormal neonatal cranial shape and early developmental delays manifested in both conditions remains poorly understood.